Nosocomial hepatitis A outbreak among healthcare workers and patients in a community hospital during an ongoing statewide outbreak. (3rd February 2021) - Brennan, Julia; Mullins, Heather; Tobey, Kelley; Jones, Cassandra; Kainer, Marion A.; Fiscus, Michelle; May, Stephen; Dunn, John R.; Schaffner, William; Jones, Timothy F.
Abstract: Objective: The Tennessee Department of Health (TDH) investigated a hepatitis A virus (HAV) outbreak to identify risk factors for infection and make prevention recommendations. Design: Case series. Setting: Community hospital. Participants: Healthcare workers (HCWs) or patients with laboratory-confirmed acute HAV infection during October 1, 2018–January 10, 2019. Methods: HCWs with suspected or confirmed hepatitis A infections were interviewed to assess their exposures and activities. Patient medical records and hospital administrative records were reviewed to identify common exposures. We conducted a site investigation to assess knowledge of infection control practices among HCWs. Serum specimens from ill persons were tested for HAV RNA by polymerase chain reaction (PCR) and genotyped. Results: We identified 6 HCWs and 2 patients with laboratory-confirmed HAV infection. All cases likely resulted from exposure to a homeless patient with a history of recreational substance use and undiagnosed HAV infection. Breaches in hand hygiene and use of standard precautions were identified. HAV RNA was detected in 7 serum specimens and all belonged to an identical strain of HAV genotype 1b. Conclusions: A hepatitis A outbreak among hospital patients and HCWs resulted from exposure to a single patient with undiagnosed HAV infection. Breakdowns in infection control practices contributed to the outbreak. The likelihood of nosocomial transmission can be reduced with proper hand hygiene, standard precautions, and routine disinfection. During community outbreaks, medical providers can better prevent ongoing transmission by including hepatitis A in the differential diagnosis among patients with a history of recreational substance use and homelessness.